Iridium(I)-Catalyzed Isoindolinone-Directed Branched-Selective Aromatic C–H Alkylation with Simple Alkenes - Maoqian Xiong; Yuhang Shu; Jie Tang; Fan Yang; Dong Xing (Molecules, 2022)
We report an iridium(I)-catalyzed branched-selective C–H alkylation of N-arylisoindolinones with simple alkenes as the alkylating agents. The amide carbonyl group of the isoindolinone motif acts as the directing group to assist the ortho C–H activation of the N-aryl ring. With this atom-economic and highly branched-selective protocol, an array of biologically relevant N-arylisoindolinones were obtained in good yields. Asymmetric control was achieved with up to 87:13 er when a BiPhePhos-like chiral ligand was employed.